PENGUATAN ORIENTASI KECINTAAN NKRI DI PERBATASAN KALIMANTAN BARAT-SERAWAK - Herawati, Netty; Sunyata, Lina (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2013)
The border region is a leading foothold in projecting the countryâs defense forces. It does not only serve as physical sovereigntyâs boundary, but also as âfrontierâ or avant garde to expand influence (sphere of influence) in articulating the national interest defense dimension. Relating to the role and position of the border region the concept of nationalism in the public dissemination of the border line of defense is needed in order to face the threat of a dimensionless nirmiliter economic, political, technological and socio-cultural values that can threaten the stability and existence of the state. Explorative qualitative research methods that take location in West Kalimantan-Sarawak border shows that: (a). National insight of the border line society is strong enough in moral aspects but weak in intellectual aspects. Weak understanding and application of the concept of nationalism from the intellectual aspect of environmental factors supported a minimal border infrastructure as well as the patterns of interaction that are inferior-superior to the citizens of Malaysia, over time is expected to decrease the sense of love and orientation to the Homeland; (b). Society still lags well as being away from the centers of economic growth into one of the countryâs defense weak point; (c). Socialization national insight through strategy communicators, audiences approach, analysis of information needs as well as packaging the message, message simplification and modification message to the people of the border line to ensure the effective dissemination to strengthen the concept of nationalism and love for the Homeland orientation in order to strengthen the countryâs defense system